2005
DOI: 10.1577/m04-012.1
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Jaw Tag Loss on Exploitation Estimates for Lake Erie Walleyes

Abstract: We used mark-recapture data collected from 1992 to 1995 to evaluate the potential effects of jaw tag loss on exploitation (u) estimates for walleyes Sander vitreus migrating from Lake Erie into the Grand River, Ohio. Loss of small jaw tags (size 10) detected during tagging periods was less than 17%. The annual loss rate of small tags exceeded 49% during each of the 2 years in which they were used. We detected no loss of large tags (size 12) during tagging periods, and annual rates of large-tag loss ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Our estimated exploitation rates were 4.9% higher when we accounted for the 4.7% tag loss and 28.0% higher when we accounted for the 21.9% tag loss. These results are comparable to other studies that reported estimates of Walleye exploitation increasing by 25-59% after accounting for tag loss (Kallemeyn 1989;Isermann and Knight 2005).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our estimated exploitation rates were 4.9% higher when we accounted for the 4.7% tag loss and 28.0% higher when we accounted for the 21.9% tag loss. These results are comparable to other studies that reported estimates of Walleye exploitation increasing by 25-59% after accounting for tag loss (Kallemeyn 1989;Isermann and Knight 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Kallemeyn (1989) reported that estimates of Walleye population size decreased by approximately 8.5% after accounting for 24.2% tag loss rates, and Isermann and Knight (2005) documented exploitation rates that were 25-59% higher after accounting for tag loss. Ebener and Copes (1982) calculated exploitation and fishing mortality rates that were 17% higher after accounting for tag loss, and these increases led to a 40% increase in yield-per-recruit model outputs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We calculated exploitation rates of the total number of individuals in the population (E i ) for each year using estimates of walleye harvest from the creel surveys (Larson et al 1991;Pierce et al 1995;Isermann and Knight 2005):…”
Section: Exploitation Rate Calculationsmentioning
confidence: 99%